1988
DOI: 10.1017/s0047404500013105
|View full text |Cite
|
Sign up to set email alerts
|

Forms of address in post-revolutionary Iranian Persian: A sociolinguistic analysis

Abstract: The sudden shift from power to solidarity in Iran in the face of the sociopolitical upheaval in the country has yielded some interesting changes in the forms of address in Persian. In general, since the Islamic Revolution of 1979, forms of address in Persian have undergone a sociolinguistic simplification. In post-revolutionary Iran plain speech and forms of address marking solidarity have gained popularity, whereas asymmetrical forms reflecting the complex social class structure of pre-revolutionary Iran have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 8 publications
1
14
0
1
Order By: Relevance
“…Comparison of the results shows that in formal situations sex is a stronger determiner in the use of forms of address in Persian. This con®rms the claim made elsewhere (Keshavarz 1988) that in interaction with members of the opposite sex in the Iranian culture people tend to be more polite and deferential; that is, a greater amount of social distance is maintained. …”
Section: Comparisons Of Interest Here Include Interactions Between Spsupporting
confidence: 86%
“…Comparison of the results shows that in formal situations sex is a stronger determiner in the use of forms of address in Persian. This con®rms the claim made elsewhere (Keshavarz 1988) that in interaction with members of the opposite sex in the Iranian culture people tend to be more polite and deferential; that is, a greater amount of social distance is maintained. …”
Section: Comparisons Of Interest Here Include Interactions Between Spsupporting
confidence: 86%
“…Keshavarz (1988) conducted a study of the forms of address in post-revolutionary Iran. In search for the political function of address terms, he reports that the revolution in Iran resulted in the choice of address terms indicating solidarity and the need to express solidarity led to greater use of terms like 'bother' and 'sister'.…”
Section: Conceptual Framework and Review Of The Related Literaturementioning
confidence: 99%
“…Likewise, several analyses have been performed on address terms in Persian language: In his study, Keshavarz (1988Keshavarz ( , 1993 found that since the 1979 Iranian revolution, address terms that show solidarity and simple kind of speech have been more widespread. In another study, he examined the effect of distance, intimacy and social context on Persian address forms and pronominal selection.…”
Section: Literature Reviewmentioning
confidence: 99%